2020
DOI: 10.3389/fpsyg.2020.00703
|View full text |Cite
|
Sign up to set email alerts
|

Toward Further Understanding of Crohn’s Disease-Related Fatigue: The Role of Depression and Emotional Processing

Abstract: Because the relationship between Crohn's Disease (CD) activity and CD-related fatigue remains poorly understood, this study investigated the role of underlying psychological processes (depression, anxiety, and emotional processing). It was expected that the relationship between CD activity and CD-related fatigue would be mediated by depression and anxiety and also by a deficit in emotional processing. This prediction was tested in 110 CD patients who completed self-reported questionnaires assessing fatigue (FS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…A more detached bodily experience of emotions may allow patients to avoid confronting overly intense physiological sensations and thereby reduce psychological distress. Consistent with this interpretation, a recent study by Banovic et al (55) found stronger emotional avoidance and emotional suppression among Crohn's disease patients than among healthy controls (55). Moreover, previous studies on attachment and mentalizing in IBD revealed greater avoidance tendencies in this clinical population (38,56).…”
Section: Experience Of Arousal In the Bodymentioning
confidence: 62%
“…A more detached bodily experience of emotions may allow patients to avoid confronting overly intense physiological sensations and thereby reduce psychological distress. Consistent with this interpretation, a recent study by Banovic et al (55) found stronger emotional avoidance and emotional suppression among Crohn's disease patients than among healthy controls (55). Moreover, previous studies on attachment and mentalizing in IBD revealed greater avoidance tendencies in this clinical population (38,56).…”
Section: Experience Of Arousal In the Bodymentioning
confidence: 62%
“…In the context of the multivariate analysis, clinical disease activity and anxiety were significantly associated with fatigue. Many studies have found a relationship between clinical disease activity and fatigue (Banovic et al, 2020; Frigstad et al, 2018; Huppertz-Hauss et al, 2017; van Langenberg & Gibson, 2014). Endoscopic disease activity was significant in univariate analysis but became nonsignificant in the multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of anxiety and depression has been associated with fatigue (Banovic et al, 2020; Borren, Long, et al, 2020; Chavarria et al, 2019; Huppertz-Hauss et al, 2017). Our results found that anxiety, but not depression, was associated with fatigue, although this finding was not maintained in the sensitivity analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 120 outpatients with IBD (57% with CD and 41% with UC), depression was reported in 22% of subjects, and the risk of developing depression in multivariate analysis was independently associated with a lack of social support and an increase in IBD disease activity [19]. CD activity was signi cantly associated with fatigue, depression, and emotional regulation [20]. All these data underline the correlation between IBD and the severity of psychiatric disorder and suggest that active IBD may exacerbate anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%